Analisis Pengaruh Pelatihan Profesional, Pertimbangan Pasar, Personalitas dan Lingkungan Kerja Terhadap Pemilihan Karir Mahasiswa Akuntansi Menjadi Akuntan Publik - Arisandi, Modelan Bilallimanto Yovi; Mawardi, M. Cholid; Sari, Arista Fauzi Kartika (e_Jurnal Ilmiah Riset Akuntansi, 2024)
The purpose of this study is to find out how accounting students perceive career choices as public accountants and whether Professional Training, Market Considerations, Personality and Working Environment have a related impact on the career benchmark of accountancy students in working as public accounts. This research adopts a quantitative approach, using primary data. Purposive sampling method is applied to obtain data based on established criteria, involving 100 respondents. The results of the research of the research show that Professional Training, Market Considerations, Personality and Working Environment have a significant positive influence on the career choices of accounting students becoming public accountants. One of the indicators that influenced this is the Market Consideration.Keywords: Career choices, professional training, market consideration, and working environment